2019
DOI: 10.3389/fmars.2019.00019
|View full text |Cite
|
Sign up to set email alerts
|

Yes, We Can! Large-Scale Integrative Assessment of European Regional Seas, Using Open Access Databases

Abstract: Substantial progress has been made in assessing marine health in an integrative way. However, managers are still reluctant in undertaking such assessments, because: (i) lack of indicators; (ii) absence of targets; (iii) difficulty of aggregating indicators from different ecosystem components, habitats, and areas; (iv) absence of criteria on the number of indicators to be used; (v) discussion on the use of "one-out, all-out" (OOAO) principle in aggregating; and (vi) lack of traceability when integrating data. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…In well-studied areas, such as the western Mediterranean, the plethora of indicators used (Teixeira et al, 2016) makes comparisons difficult, impairing the potential to obtain a reliable and extensive picture of the situation of the main benthic ecosystems. There is an urgent need to achieve a general consensus on which data and which indicators have to be used to classify the status of marine ecosystem health (Miloslavich et al, 2018), and further attempts to integrate and gather existing information (e.g., Borja et al, 2019;. Current practices are too fragmented depending on decisionmakers, researchers, and practitioners' preferences or interests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In well-studied areas, such as the western Mediterranean, the plethora of indicators used (Teixeira et al, 2016) makes comparisons difficult, impairing the potential to obtain a reliable and extensive picture of the situation of the main benthic ecosystems. There is an urgent need to achieve a general consensus on which data and which indicators have to be used to classify the status of marine ecosystem health (Miloslavich et al, 2018), and further attempts to integrate and gather existing information (e.g., Borja et al, 2019;. Current practices are too fragmented depending on decisionmakers, researchers, and practitioners' preferences or interests.…”
Section: Discussionmentioning
confidence: 99%
“…The achievement and maintenance of good ecological conditions requires large-scale management of human activities and their ensuing pressures to marine ecosystems (Borja et al, 2019;Mazaris et al, 2019). CEA approaches, through mapping estimated cumulative impacts, could represent a powerful tool in this view, especially if embedded in a risk management process (Stelzenmüller et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Remote sensing is too infrequently employed at a global scale to create a reliable and usable monitoring platform system, however, it remains a promising technique for monitoring water quality (Matthews et al, 2010). Furthermore, progress through new technologies, e.g., the Nested Environmental status Assessment Tool, is improving the ability to aggregate and disaggregate existing data at scales that bridge gaps between marine systems and the people who depend upon them (Borja et al, 2019).…”
Section: Large-scale Data Collection Integration and Disseminationmentioning
confidence: 99%
“…Open science has also influenced how research workflows are conceptualized in other disciplines (e.g., archaeology, Marwick et al, 2016 , behavioral ecology, Ihle et al, 2017 , hydrology, Slater et al, 2019 , vegetation sciences, Collins, 2016 ) and has enabled a shift towards publishing structures that are more fair and transparent through open access ( Van Oudenhoven, Schröter & De Groot, 2016 ; Essl et al, 2020 ). Limited examples have suggested that open access databases can be leveraged to develop bioassessment products that increase transparency among stakeholders ( Borja et al, 2019 ). Adopting an open science paradigm in bioassessment is particularly relevant compared with other fields given the explicit need to develop products that are accessible to the management community.…”
Section: Introductionmentioning
confidence: 99%